Current clinical management of smoke inhalation injuries: a reality check. Issue 6 (6th December 2018) - Spinou, Arietta; Koulouris, Nikolaos G.
A major disaster is happening at the moment, as the Camp Fire, Woolsey Fire and Hill Fire are burning in California. Camp Fire in Northern California has already burned 546.3 km 2 and is the deadliest wildfire in the history of the state, with 48 fatalities and still counting [1]. It was also only recently, in July 2018, when a fire entered the populated area of Mati, Greece, and created a wildland urban interface that caused 99 fatalities and numerous burns and smoke inhalation injuries. A few years ago, in August 2007, 67 people died in a megafire event in the Peloponnese region, Greece, which was created by 55 simultaneous large fires (based on size, intensity, environmental and socio-economic impact) [2]. These and numerous other tragic incidents highlight the importance of our current clinical management of the victims of fire. Smoke inhalation injury is a complex clinical condition and respiratory clinicians need to have a good understanding of its current clinical management. However, evidence derives mostly from retrospective cohorts and case series. Is this enough? http://ow.ly/PrtT30mJcYD